Two Decades of Maude - Clavel, Manuel; Durán, Francisco; Eker, Steven; Escobar, Santiago; Lincoln, Patrick; Martí-Oliet, Narciso; Talcott, Carolyn (My University, 2015)
This paper is a tribute to José Meseguer, from the rest of us in the Maude team, reviewing the past, the present, and the future of the language and system with which we have been working for around two decades under his leadership. After reviewing the origins and the language's main features, we present the latest additions to the language and some features currently under development. This paper is not an introduction to Maude, and some familiarity with it and with rewriting logic are indeed assumed.
Keywords: Maude (Lenguaje de programación)